The Labor Market in the Great Recession: An Update - Michael W.L. Elsby; Bart Hobijn; Aysegul Sahin; Robert G. Valletta (Tinbergen Institute, 2011)
Since the end of the Great Recession in mid-2009, the unemployment rate has recovered slowly, falling by only one percentage point from its peak. We find that the lackluster labor market recovery can be traced in large part to weakness in aggregate demand; only a small part seems attributable to increases in labor market frictions. This continued labor market weakness has led to the highest level of long-term unemployment in the U.S. in the postwar period, and a blurring of the distinction between unemployment and nonparticipation. We show that flows from nonparticipation to unemployment are important for understanding the recent evolution of the duration distribution of unemployment. Simulations that account for these flows suggest that the U.S. labor market is unlikely to be subject to high levels of structural long-term unemployment after aggregate demand recovers.
urn:NBN:nl:ui:31-1871/38564
Keywords: E24; J2; 330; Labor market dynamics; long-term unemployment; unemployment duration; Arbeitsmarkt; Langzeitarbeitslosigkeit; Gesamtwirtschaftliche Nachfrage; Arbeitslosigkeit; Konjunktur; Wirtschaftskrise; USA